Penyesuaian Kurikulum dengan Strategi Gradasi dalam Pembelajaran Bahasa Arab untuk Siswa ADHD - Laili Mas Ulliyah Hasan; Muhammad Tareh Aziz; Muhammad Rido’i (Pascasarjana Universitas Qomaruddin, 2024)
This study aims to develop a graded Arabic language curriculum on the theme “Visiting the Sick” for ADHD students, focusing on structuring the material progressively from simple to complex and from concrete to abstract concepts. We used descriptive qualitative research with a case study approach to collect data through classroom observation, teacher interviews, and curriculum document analysis. The grading stages begin with the introduction of basic vocabulary and simple phrases, progressing to sympathetic expressions, etiquette in visiting, and finally to social and spiritual reflections on health. The findings indicate that this graded material is effective in helping ADHD students gradually understand and master Arabic, with significant improvements in their speaking skills, cultural comprehension, and empathetic abilities toward patients. Implementing a curriculum that considers social and cultural aspects of the Arabic language aligns with Vygotsky’s theory on the importance of social interaction in learning and Bronfenbrenner’s theory on the influence of cultural context. Thus, graded material can enhance the effectiveness of Arabic language learning for ADHD students in an inclusive school setting.